Course in domestic science for a first-year, high school student - Taylor, Irene (My University, 1908)
Introduction: This outline is meant to be a working outline. One from which the teacher can plan her lessons and add or detract from the theory part as seems desirable. The pupils work in groups of two, but individual work is given wherever possible.
Citation: Taylor, Irene. Course in domestic science for a first-year, high school student. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Education; Domestic Science; Home Economics; High School; Graduating theses; Senior theses; Theses